Manganese and selenium co-doped CeO2@Co3O4 porous core–shell nanospheres for enhanced oxygen evolution reactions. (27th January 2023) - Huang, Xianggang; Wang, Xin; Zhang, Mengling; Jiang, Qilei; Qin, Zheng; Liu, Yingxin; Hou, Yan; Cao, Xueqin; Gu, Hongwei
Abstract : MnSe–CeO2 @Co3 O4 synthesised by a one-pot multi-step method, followed by calcination and selenization treatments, exhibits superior electrocatalytic activity and stability. Abstract : As one of the semi-reactions of water splitting, electrocatalytic oxygen evolution reactions (OERs) are key process to generate sustainable energy. Co-based spinel oxides are deemed as promising OER electrocatalysts, but the low intrinsic activity limits their further practical applications. Herein, we report an effective strategy to synthesize CoCeMn coordination-driven self-assembled aggregates (CDSAAs) by a one-pot multi-step method. It is different from the common mixed addition method to synthesize trimetallic nanomaterials. Subsequently, CoCeMn-CDSAAs served as self-templates, and Mn and Se co-doped CeO2 @Co3 O4 porous core–shell nanospheres (MnSe–CeO2 @Co3 O4 ) were obtained after calcination and selenization treatments. It is worth mentioning that CeO2 and the doping Mn/Se elements increase the oxygen vacancy content and the ratio of Co 3+ /Co 2+ on the surface respectively and can effectively accelerate the four-electron transfer process of OERs. Moreover, the special porous core–shell structure exposes more active sites and is also useful for boosting OER performance. When explored as an anode electrocatalyst for OERs, MnSe–CeO2 @Co3 O4 exhibits excellent OER performance (284 mV@10 mA cm −2 ) and a long-time stability of 40 h in an alkaline medium. This work provides a feasible idea for the construction of multi-component porous core–shell nanoelectrocatalysts with non-noble metals.